ANALISIS FUNGSI INVESTASI PADA SEKTOR INDUSTRI MANUFAKTUR DAN DAMPAK INVESTASI PADA KEBUTUHAN IMPOR INDONESIA - Ahmad Jamli; Firmansyah Firmansyah (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
Investment as one of crucial production factor, plays a big role in increasing production as shown through economic growth. In other words, investment becomes a shift variable or a loco of national economic activities. During the I Long-run Development and in the beginning of 2nd Long-run Development, the investment both PMDN and Foreign Investment Company (PMA) has grown rapidly, especially in the manufacturing industry which becomes a prime sector of national development. Dependency of National production sector –especially manufacturing industry sector-to raw materials and capital goods from abroad has caused import of those are increasing as well as the increasing of investment demand.Besides supported by regulations and debureaucratisation which has done by the government, the demand to invest their capital is determined by macroeconomic variables, i.e. interest rate, economic growth, exchange rate and inflation.By using regression analysis with pooling data method, this study will explore the behavior of several macroeconomic variables on investment in the manufacturing industry. Using Input-Output method, this study will find out the impact of investment on changing in manufacturing industry on its import demand itself or on overall Indonesia s demand.st